Valuations in Corporate Takeovers and Financial Constraints on Private Targets - Greene, Daniel (Journal of Financial and Quantitative Analysis, 2017)
I examine acquisitions of private firms by public acquirers to better understand the effects of financial constraints on the division of economic gains in takeovers. Empirical tests exploit interstate bank branching deregulation, which relaxes financial constraints on private firms and can strengthen their bargaining position in an acquisition. Using a proxy for the degree to which targets depend on acquirers for financing, I find that private targets depend less on acquirers as a result of interstate bank branching deregulation. Relaxing financial constraints on private targets leads to an increase in target valuation multiples and a decrease in acquirer wealth gains.